A first look at the metabolic rate of Greenland sharks (Somniosus microcephalus) in the Canadian Arctic - Ste-Marie, E; Watanabe, YY; Jayson Semmens; Marcoux, M; Hussey, NE (2020)
Metabolic rate is intricately linked to the ecology of organisms and can provide a framework to study the behaviour, life history, population dynamics, and trophic impact of a species. Acquiring measures of metabolic rate, however, has proven difficult for large water-breathing animals such as sharks, greatly limiting our understanding of the energetic lives of these highly threatened and ecologically important fish. Here, we provide the first estimates of resting and active routine metabolic rate for the longest lived vertebrate, the Greenland shark ( Somniosus microcephalus ). Estimates were acquired through field respirometry conducted on relatively large-bodied sharks (33–126 kg), including the largest individual shark studied via respirometry. We show that despite recording very low whole-animal resting metabolic rates for this species, estimates are within the confidence intervals predicted by derived interspecies allometric and temperature scaling relationships, suggesting this species may not be unique among sharks in this respect. Additionally, our results do not support the theory of metabolic cold adaptation which assumes that polar species maintain elevated metabolic rates to cope with the challenges of life at extreme cold temperatures.